"The Click-Clack of Her Heels and the Jingle of Her Keys": Exploring the Tensions in the Leadership of a Successful Turnaround Principal. Issue 4 (July 2017) - Reitzug, Ulrich C.; Hewitt, Kimberly Kappler
This qualitative case study explores the practices and tensions of being an effective principal in a turnaround school through an in-depth analysis of one principal who has been successful in several turnaround settings. Although principals have long been cited as foundational to a school's success, being the principal of a turnaround school is a significantly different enterprise than being a principal of a non-turnaround school. Newly appointed turnaround principals are expected not only to generate significant improvement in achievement in schools that have been low-achieving for many years, but to do so in a short period of time. To gain insight into the leadership practices of a principal who was successful in accomplishing school turnaround, we conducted interviews with 21 of the principal's current and past colleagues, observed her in practice, analyzed documents related to her leadership, and interviewed her three times. In this report, we describe her leadership practice and conclude that it was characterized by four dynamic tensions that resulted in the turnaround of the schools she led: The tension between focusing on mission and focusing on personal connection; The tension between high expectations and high trust and respect; The tension between strong principal presence and strong staff presence; and The tension between disrupting complacency and continuity. We conclude by arguing that a key to effective practice for turnaround principals lies in their creating ongoing dynamic tensions in their schools.